Strategies for the translation of modal auxiliary verbs as hedging devices in newspaper articles on climate change - Morales Triana, Marilín; Rodríguez Ruiz, Mayra (Feijóo, 2021)
Translation has been used for foreign language teaching since the 19th century when modern languages began to appear in school curricula. Its strength on the field of foreign language teaching resides in the fact that is used to demonstrate the learner's knowledge of the foreign language, either as a form of control or to exercise his intelligence in order to develop his competence. One of the main problems for translation students is their difficulties to translate certain pragmatic elements of the text such as hedging devices. This could lead to errors in comprehending the text’s ideas and the author’s initial intentions. During the process of translation, when a problem emerges, translators need to put into practice strategies to solve such problem. A translation strategy is a conscious problem solving procedure that comes from the translator’s previous knowledge. As stylistic devices, hedges are embedded in several discourses. The present research focuses on hedges in journalistic discourse because it has not received much attention among scholars. This research is aimed at identifying the strategies most commonly used for the translation of hedging devices used in online English newspaper articles on climate change. It is carried out through a comparative analysis of a parallel English-Spanish corpus compiled from the newsroom of present in the websites of different international and regional environmental agencies. Finally, it presents a set of strategies for the translation of hedging devices that can help improve the teaching and learning process in the subject of Translation of Journalistic Texts.

Desde que el estudio de lenguas modernas se incluyó los planes de estudio en el siglo XIX, la traducción se utilizó para la enseñanza de idiomas. Su fortaleza en este campo es que demuestra el conocimiento de la lengua extranjera que poseen los estudiantes, ya sea como un método para controlar o para ejercitar su inteligencia encaminado a desarrollar dicha competencia. Uno de los principales problemas que presentan los estudiantes durante el proceso de traducción es que a menudo son incapaces de traducir ciertos elementos pragmáticos del texto como los matizadores discursivos. Esto puede llevar a errores en la comprensión de las ideas del texto y las intenciones iniciales del autor. Cuando surge un problema, el traductor debe poner en práctica estrategias para solucionarlo. Una estrategia de traducción es un procedimiento consciente para la solución de problemas que parte del conocimiento previo del traductor. Como recursos estilísticos, los matizadores se encuentran en varios discursos. El presente estudio se centra en los matizadores presentes en el discurso periodístico. El objetivo de esta investigación es identificar las estrategias más comunes para la traducción de matizadores en artículos periodísticos en línea escritos originalmente en inglés sobre el cambio climático. Se realiza sobre la base de un análisis comparativo de un corpus paralelo inglés-español compilado a partir de los sitios web de varias agencias medioambientales. Finalmente, el mismo presenta un conjunto de estrategias para la traducción de los matizadores que puede mejorar el proceso de enseñanza- aprendizaje en la asignatura de Traducción de Textos Periodísticos.
Estrategias para la traducción de verbos modales auxiliares como matizadores discursivos en artículos periodísticos sobre cambio climático
Keywords: Translation; Translation Theory; Translation Strategy; Hedging Device; Corpus Linguistics; Traducción; Teoría de Traducción; Estrategia de Traducción; Matizador Discursivo; Lingüística de Corpus; Discurso Periodístico; Lengua Inglesa